2013
DOI: 10.1002/aenm.201300844
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Properties of Polymer Electrolyte‐Based Stretchable Supercapacitors

Abstract: Aligned carbon nanotube (CNT) forests filled with a dehydrated polymer electrolyte are used to fabricate flexible solid state supercapacitors (SSCs) for multifunctional structural‐electronic applications. Local stiffness measurements on the composite electrodes determined through nano­indentation showed an 80% increase over the neat solid polymer electrolyte matrix. Electrochemical properties are monitored as a function of average tensile strain in the SSCs. Galvanostatic charge‐discharge tests with in situ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…During indentation, the force and displacement are continuously monitored with nanoNewton and nanometer resolution, respectively, making the technique attractive for applications in which small volumes of materials need to be examined. Standard NI theory assumes specimens are flat, isotropic half‐spaces, although tests on substrate‐film systems, composite materials, samples with edges, and graded materials have been demonstrated with appropriate modifications. Indentation studies accounting for viscoelastic behavior of materials have also been demonstrated; a particularly challenging issue for applying depth‐sensing indentation to a material with time‐dependent mechanical behavior is creep, which can complicate the assumed linear elastic response during the initial stages of unloading …”
Section: Introductionmentioning
confidence: 99%
“…During indentation, the force and displacement are continuously monitored with nanoNewton and nanometer resolution, respectively, making the technique attractive for applications in which small volumes of materials need to be examined. Standard NI theory assumes specimens are flat, isotropic half‐spaces, although tests on substrate‐film systems, composite materials, samples with edges, and graded materials have been demonstrated with appropriate modifications. Indentation studies accounting for viscoelastic behavior of materials have also been demonstrated; a particularly challenging issue for applying depth‐sensing indentation to a material with time‐dependent mechanical behavior is creep, which can complicate the assumed linear elastic response during the initial stages of unloading …”
Section: Introductionmentioning
confidence: 99%
“…The technique has been used to characterize the elastic modulus, elastic-plastic stress-strain curves, creep properties, and hardness of a wide range of materials and structures, including traditional steels [50], film-substrate systems [51], functionally graded structures [52,53], polymers and polymer composites [54][55][56], and individual microfibers [57]. In the current study, the local stiffness properties of the beam samples near the fixed boundary were examined using nanoindentation (Figure 8).…”
Section: Local Mechanical Characterizationmentioning
confidence: 99%
“…Among the family of carbon nanomaterials, CNFs, CNTs and graphene have achieved great attention due to their unique features such as a large surface area to volume ratio, good electronic conductivity, excellent stability, etc. In addition, they are found to be useful in manufacturing various nanocomposites since they can form entangled network during their preparation to improve the electrode conductivity [33]. The technological advancements in the field of nanoscience helped the developments of high power EDLCs, but the lack of energy density remains a big challenge.…”
Section: Strategies For High-performance Supercapacitorsmentioning
confidence: 99%